Seven ways to fix policing now: building trust, authentic partnerships, and safe communities - O'Toole, Kathleen (Rowman & Littlefield, 2022)
"The time has come to take a comprehensive look at every aspect of policing. This book does that and offers seven critical steps towards successful and sustainable police reform"--